ACHIEVING ADEQUACY IN RENDERING ENGLISH IDIOMS AND PHRASEOLOGICAL UNITS INTO UZBEK ( BASED ON AGATHA CHRISTIE'S WORKS) (International Conference on Economics, Finance, Banking and Management, 2025)
The problem of achieving adequacy in the presentation of English idioms and phraseological units to the Uzbek language occupies an important place in the field of linguistic research and translation theory. This issue becomes more relevant, especially when translating texts rich in complex cultural and linguistic identities, such as the works of Agatha Christie. Idioms and phraseological units serve as cultural codes of language, which include not only the meaning of words, but also the spiritual-emotional and cultural context. Therefore, when changing them to another language, not only a lexical equivalent should be provided, but also cultural and contextual compatibility.